Organomineral as a substitute for mineral fertilization in potato cultivation - Oliveira, Roberta Camargos de; Almeida , Risely Ferraz; Oliveira , Pedro Lucas Santos; Silva, Jarbas Reis; Luz , José Magno Queiroz (Comunicata Scientiae, 2023)
Potato (Solanum tuberosum, L.) is one of the most responsive crops to fertilizer application, which drives the need to rationalize and make the most of nutritional resources in efficient and sustainable management. Based on the hypothesis that the organomineral is a great alternative to increase potato productivity (Ágata and Atlantic cultivars) and that it can be indicated as a substitute for mineral fertilizers, this study aims to evaluate the effect of organomineral doses applied in the planting furrow on potato productivity to identify the best level of mineral fertilizer replacement. A study was conducted in the city of Cristalina (state of Goiás, Brazil), evaluating the replacement of 40, 60, 80, and 100% of mineral fertilizer (standard) provided via organomineral fertilizer in two widely cultivated varieties. The total productivity and the productivity in classes were monitored, as well as the nutrient contents in the leaves. The results showed that the organomineral is a great alternative to increase potato productivity and can be indicated as a substitute for mineral fertilizers. For the cultivar Ágata, an organomineral dose of 80% is recommended concerning mineral fertilization. On the other hand, for the Atlantic cultivar, the same dose of mineral fertilizer is recommended. In both cultivars, there was an increase in tuber size with organomineral fertilization, which indicates greater efficiency in tuber productivity.